Formulation of a Commercial Biosurfactant for Application as a Dispersant of Petroleum and By-products Spilled in Oceans - Freitas, Bruno G.; Brito, Juliana M.; Brasileiro, Pedro P.; Rufino, Raquel D.; Luna, Juliana M.; Santos, Valdemir A.; Sarubbo, Leonie A. (Frontiers in Microbiology, 2016)
Oil spills in oceans cause irreparable damage to marine life and harm the coastal populations of affected areas. It is therefore fundamental to develop treatment strategies for such spills. Currently, chemical dispersants have been used during oil spills, although these agents have been increasingly restricted due to their toxic potential. Thus, the aim of the present study was to formulate a biodegradable commercial biosurfactant for application as a dispersant. Biosurfactants are scientifically known biomolecules produced by microorganisms capable of allowing water-oil interaction. Thus, a biosurfactant was produced by the yeast Candida bombicola URM 3718 cultivated in industrial waste and formulated with the addition of a potassium sorbate preservative for fractionated sterilisation (tyndallisation) and the combination of fluent vaporisation with the preservative. After formulation, samples were stored for 120 days, followed by surface tension, emulsification and oil dispersant tests in sea water. The results were promising for the biosurfactant formulated with the preservative, which demonstrated stability and an absence of toxicity in experiments with a marine indicator. The commercial biosurfactant was tested at different pH values, temperatures and in the presence of salt, demonstrating potential industrial application at a cost compatible with the environmental field. The formulation process developed in this research was patented in the Brazilian National Intellectual Property Institute (patent number BR1020140179631).